Fighting against AtroCITIES in the land of the free: why black lives, geography and democracy should matter to America - Kempe, Leo (2021)
Black lives are connected to geography and politics, particularly in the United States, its cities and neighborhoods. Often initiated by Whites, detrimental practices of racialization, alienation and opportunity deprivation can be observed on various scales. Importantly, these realities are connected to human rights and thus a fundament for democracy. This thesis uses a triangulation of the three variables Black lives, geography and democracy to answer the question of how the first two influence democratic stability in the United States. In the context of the Black Lives Matter Movement, it focuses on racism, police violence and accessibility problems for Black people, taking the cities of Minneapolis, Minnesota and Washington, D.C. as illustrations. These proved to be relevant because of the murder of George Floyd and the anti-discrimination White House protests, respectively. Theoretical orientations from Black Geographies and social justice activism facilitated assessing the two cities' contribution to democracy, and it is concluded that through relational analysis we can better understand the significance of the three interdependent variables for the country.
Keywords: Amerika; Hochschulschrift